2002
DOI: 10.1002/chin.200229024
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Equilibrium Data for the Exchange of Cu2+, Cd2+, and Zn2+ Ions for H+ on the Cationic Exchanger Amberlite IR‐120.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 1 publication
1
10
1
Order By: Relevance
“…Several studies ,,,, have shown that the mass action law is efficient to represent equilibrium in ion exchange for different systems. However, the mass action law was used in some studies to represent the equilibrium in the dynamics of the fixed-bed column only. ,, Nevertheless, these works considered an ideal behavior that means that all sites are available to the exchanging process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies ,,,, have shown that the mass action law is efficient to represent equilibrium in ion exchange for different systems. However, the mass action law was used in some studies to represent the equilibrium in the dynamics of the fixed-bed column only. ,, Nevertheless, these works considered an ideal behavior that means that all sites are available to the exchanging process.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have successfully used the Wilson model to calculate the activity coefficients of ionic species in the solid phase.…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…Semitheoretically approaches to investigate the role of temperature on ion exchange equilibria have been investigated by a number of researchers. Barri et al investigated the binary and ternary cation exchange in zeolites involving Na + , Ca 2+ and Mg 2+ at 25 and 65 °C. They fitted the corrected selectivity coefficient ( K c ) data to polynomial equations and then from these equations, thermodynamic parameters were calculated.…”
Section: Introductionmentioning
confidence: 99%
“…They agreed that Wilson’s model was slightly better. Several investigators , have successfully used Wilson’s model to calculate the activity coefficient of the species in the resin phase.…”
Section: Introductionmentioning
confidence: 99%
“…Shallcross et al were among the first to use this model to calculate the activity coefficients of ions in solution to represent the equilibrium of ionic exchange processes by the Mass Action Law. Later, Pitzer’s model was used by several authors ,,,, to calculate the activity coefficients in the solution phase.…”
Section: Introductionmentioning
confidence: 99%